Toward Minimum Standards for Certifying Patient Decision Aids: A Modified Delphi Consensus Process. (August 2014) - Joseph-Williams, Natalie; Newcombe, Robert; Politi, Mary; Durand, Marie-Anne; Sivell, Stephanie; Stacey, Dawn; O'Connor, Annette; Volk, Robert J.; Edwards, Adrian; Bennett, Carol; Pignone, Michael; Thomson, Richard; et al.
Objective. The IPDAS Collaboration has developed a checklist and an instrument (IPDASi v3.0) to assess the quality of patient decision aids (PDAs) in terms of their development process and shared decision-making design components. Certification of PDAs is of growing interest in the US and elsewhere. We report a modified Delphi consensus process to agree on IPDASi (v3.0) items that should be considered as minimum standards for PDA certification, for inclusion in the refined IPDASi (v4.0). Methods. A 2-stage Delphi voting process considered the inclusion of IPDASi (v3.0) items as minimum standards. Item scores and qualitative comments were analyzed, followed by expert group discussion. Results. One hundred and one people voted in round 1; 87 in round 2. Forty-seven items were reduced to 44 items across 3 new categories: 1) qualifying criteria, which are required in order for an intervention to be considered a decision aid (6 items); 2) certification criteria, without which a decision aid is judged to have a high risk of harmful bias (10 items); and 3) quality criteria, believed to strengthen a decision aid but whose omission does not present a high risk of harmful bias (28 items). Conclusions. This study provides preliminary certification criteria for PDAs. Scoring and rating processes need to be tested and finalized. However, the process of appraising the quality of the clinical evidence reported by the PDA should be used to complement these criteria; the proposed standards are designed to rate the quality of the development process and shared decision-making design elements, not the quality of the PDA's clinical content.